Der polymorphe Bes: Untersuchungen zu Entwicklung, Devianz und Tradition eines mehrköpfigen Wesens im alten Ägypten - Theis, Christoffer (De Gruyter, 2025)
Bes has been transmitted from Ancient Egypt as a polymorphic figure with several heads. According to the sources, he was a fairly widespread and especially popular being that was received in both royal and private contexts and used in protective rituals. This entity has been documented in many sources since the seventh century BCE, such as reliefs, statuettes, texts, and vignettes, and was even depicted on gems in late antiquity
Keywords: Hochschulschrift; Geschichte; Mythos; Ägypten; Bes